Neurodevelopmental outcomes for high-risk neonates in a low-resource setting. Issue 11 (28th August 2017) - Milner, Kate M; Duke, Trevor; Steer, Andrew C; Kado, Joseph H; Koyamaibole, Lanieta; Kaarira, Rakei; Namudu, Kelera; Woolfenden, Susan; Miller, Anne E; O'Heir, Kathryn E; Neal, Eleanor F G; Roberts, Gehan
Abstract : Worldwide, most neonates who survive prematurity and serious illness reside in low-resource settings where developmental outcome data and follow-up care are limited. This study aimed to assess in Fiji, a low-resource Pacific setting, prevalence and risk factors for moderate to severe neurodevelopmental impairment (NDI) in early childhood among high-risk neonates compared with controls. Retrospective cohort study comparing long-term outcomes for high-risk neonatal intensive care unit patients (n=149) compared with matched term, normal birth weight neonates (n=147) discharged from Colonial War Memorial Hospital between November 2008 and April 2010. NDI was defined as one or more of cerebral palsy, moderate to severe hearing or visual impairment, or global developmental delay using Bayley Scales of Infant and Toddler Development Third Edition (ie, score <70 in ≥1 of cognitive, language or motor domains). At median (IQR) age 36.1 (28.3, 38.0) months, prevalence of moderate to severe NDI % (95% CI, n) in high-risk and control groups was 12 (5 to 17, n=13) and 5 (2 to 12, n=5), respectively, an increased risk ratio (95% CI) of 2.7 (0.8 to 8.9). Median gestational age (weeks (median, IQR)) in the high-risk group was 37.5 (34–40) weeks. Among high-risk neonates, gestational age, birth weight, asphyxia, meningitis and/or respiratory distress were significantly associated with risk of NDI. Prevalence of NDI was high among this predominantly term high-risk neonatal cohort compared with controls. Results, including identified risk factors, inform efforts to strengthen quality of care and models of follow-up for high-risk neonates in this low-resource setting.